Conceptualizing trust in community-academic research partnerships using concept mapping approach: A multi-CTSA study. (February 2018) - Dave, Gaurav; Frerichs, Leah; Jones, Jennifer; Kim, Mimi; Schaal, Jennifer; Vassar, Stefanie; Varma, Deepthi; Striley, Catherine; Ruktanonchai, Corrine; Black, Adina; Hankins, Jennifer; Lovelady, Nakita; et al.
Highlights: Aim of this study was to conceptualize trust in community-academic research partnerships. Employed concept mapping approach to engage community members, healthcare providers and academicians. Conducted hierarchical cluster analysis to assess the determinants of trust. A five-cluster solution was defined to develop a framework for measuring trust. Abstract: Objectives: Collaborations between communities, healthcare practices and academic institutions are a strategy to address health disparities. Trust is critical in the development and maintaining of effective collaborations. The aim of this pilot study was to engage stakeholders in defining determinants of trust in community academic research partnerships and to develop a framework for measuring trust. Methods: The study was conducted by five collaborating National Institute of Health' Clinical and Translational Sciences Awardees. We used concept mapping to engage three stakeholders: community members, healthcare providers and academicians. We conducted hierarchical cluster analysis to assess the determinants of trust in community-academic research partnerships. Results: A total of 186 participants provided input generating 2, 172 items that were consolidated into 125 unique items. A five cluster solution was defined: authentic, effective and transparent communication; mutually respectful and reciprocal relationships; sustainability; committed partnerships; and, communication, credibility and methodology to anticipate and resolve problems. Conclusion: Results from this study contribute to an increasing empirical body of work to better understand and improve the underlying factors that contribute to building and sustaining trust in community academic research partnerships.